Fragments, Lyotard, and Earthquakes: A mosaic of memory and broken pieces. (December 2015) - Locke, Kirsten; Yates, Sarah
Abstract: This paper explores the responses by a group of children to an art project that was undertaken by a small school in New Zealand after the September 2010 and February 2011 Christchurch earthquakes. Undertaken over a period of two years, the project aimed to find a suitable form of memorialising this significant event in a way that was appropriate and meaningful to the community. Alongside images that related directly to the event of the earthquakes, the art form of a mosaic was chosen, and consisted of images and symbols that clearly drew on the hopes and dreams of a school community who were refusing to be defined by the disaster. The paper 'writes' the mosaic by placing fragments of speech spoken by the children involved in relation to ideas about memory, affect, and the 'sublime', through the work of Jean-François Lyotard. The paper explores the mosaic as constituted by the literal and metaphorical 'broken pieces' of the city of Christchurch in ways that confer pedagogic value inscribed through the creation of a public art space by children.